Relationship of ST-segment elevation myocardial infarction with weather and season - Okkes Zortuk; Fatih Selvi; Cihan Bedel; Mustafa Korkut (Medicine Science)
Myocardial infarction (MI) is a leading cause of mortality and morbidity. The most lethal subgroup of MI patients is ST-segment elevation myocardial infarction (STEMI). This study aims to investigate the relationship between STEMI patients and weather conditions, as recent studies suggest that environmental factors may contribute to the development of STEMI. The study analysed STEMI patients. The study recorded the weather conditions of patients on the days they were admitted to the hospital. The data collected included daily average air temperature (in Celsius), dew point (in Celsius), humidity (as a percentage), weather condition (fair, cloudy, windy, or rainy), wind speed (in rpm), pressure (in inches) obtained via the API where previous data is stored, and precipitation (in inches). This data was then matched with the patients. Although 8 (4.23%) of the participants died, there was no significant difference observed in the comparison of demographic and laboratory data. When comparing the impact of seasonal changes on mortality in STEMI patients, we found that the average humidity during the admission period was significantly lower for patients who did not survive (39.87±9.76) compared to those who did (p=0.022). However, we did not observe any significant effects on mortality from air temperature, Dew Point, Wind speed, Wind gust, or pressure (P value respectively; 0.506, 0.181, 0.063, 0.684). The humidity levels during the admission period significantly affect the mortality rates of STEMI patients, depending on the prevailing climatic conditions. [Med-Science 2024; 13(4.000): 835-9]